Hydrophilic Tetraphenylethene-Based Tetracationic Cyclophanes: NADPH Recognition and Cell Imaging With Fluorescent Switch - Wu, Dan; Zhang, Zhankui; Yu, Xinyang; Bai, Bing; Qi, Shaolong (Frontiers in Chemistry, 2021)
A hydrophilic TPE-based tetracationic cyclophane TPE-cyc was synthesized, which could capture intracellular NADPH and fuel the antioxidative ability of tumor cells to detoxify reactive oxygen species (ROS). Meanwhile, upon the reduction by cellular GSH, TPE-cyc could light up tumor cells, acting as a GSH-responsive fluorescent switch to image cells with high resolution.